Logistics Cost Management and Control of E-Commerce Enterprise Under the Background of IoT - Kang Wang; Zhanqiao Liu (Journal of Applied Mathematics)
Despite the rapid growth of enterprises in China, logistics costs remain a significant challenge, accounting for a large proportion of overall business expenses and hindering corporate development. Effective logistics cost management requires careful coordination of routing and resource allocation for goods transportation. Studies have highlighted several challenges faced by China’s logistics industry, including high transportation costs, complex management processes, and excessive warehousing expenses. To tackle these issues, this paper proposes an optimization model for logistics costs utilizing Internet of Things (IoT) technology. By improving the efficiency and accuracy of each stage in the logistics supply chain through advanced information processing, the model seeks to streamline supply chain operations and reduce transfer costs. Additionally, the paper explores the current state of e-commerce enterprise growth and future logistics control trends, providing strategic recommendations. These strategies include optimizing logistics information flow through IoT, developing IoT-based cost management systems for e-commerce logistics, and integrating logistics cost optimization into the strategic planning of e-commerce enterprises.